´Rocha’ pear antioxidant and mineral characterization - Coelho, Inês (2018)
Introduction: ‘Rocha’ pear (Pyrus communis L.) is a Portuguese native variety with a Protected Designation of Origin (PDO). This variety is responsible for 95% of the national pear production and represents an important economic activity1 with exportations over 67 million Euros per year2. Pears are very nutritive fruits, rich in micronutrients, antioxidants and other important nutrients. Its nutritional value has been widely studied. However, in comparison to other European pears like Bartllet and Red Anjou, whose nutritional value is well known and published in reference databases, ‘Rocha’ pear’s nutritional quality has been less studied. Objectives and methodology: The objective of this study was to evaluate an antioxidant and mineral characterization of ‘Rocha’ pear. Antioxidant capacity was characterized by testing the elimination of free radicals DPPH (2,2-diphenyl-1-picrylhydrazyl) and by the Folin-Ciocalteau method. Minerals and trace elements were quantified by ICP-MS and ICP-OES after a graphite heating block (digiprep) digestion. Elements analyzed were Cr, Mn, Co, Cu, Se, Sr, Mo, Sn, Zn, Fe, Mg, P, K, Ca and Na. ‘Rocha’ pear samples were collected from 11 farms in 2 Portuguese regions (Fundão and PDO region). Each laboratory sample was a pool of three pears. One sample was used to study differences between peel and pulp. After the removal of seeds pear samples were freeze-dried and vacuum sealed until analysis. Main findings: The PDO pears have the highest antioxidant capacity, presenting a phenolic content ranging from 0,65 to 0,84 mg eq. Galic acid/ g sample and an IC50 from 0,26 to 0,17 mg/ml. As expected the majority of compounds with antioxidant proprieties are in the peel, with proximally two times more than the pulp. In terms of micronutrients no significant differences were found between the regions under study. The exception is zinc and sodium that presents higher values for the PDO region. Conclusions: In conclusion, it is important to study and to divulge the Portuguese pear in a higher extension, once it will lead to a higher consumption by the population and consequently to a national economic growth.